2018
DOI: 10.1002/1873-3468.13075
|View full text |Cite
|
Sign up to set email alerts
|

The AAA protein spastin possesses two levels of basal ATPase activity

Abstract: The AAA ATPase spastin is a microtubule-severing enzyme that plays important roles in various cellular events including axon regeneration. Herein, we found that the basal ATPase activity of spastin is negatively regulated by spastin concentration. By determining a spastin crystal structure, we demonstrate the necessity of intersubunit interactions between spastin AAA domains. Neutralization of the positive charges in the microtubule-binding domain (MTBD) of spastin dramatically decreases the ATPase activity at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A heterozygous mutation in SPG7/PGN gene at 16q24 is characterised by extensive weakness and spasticity in lower extremities due to axonal degeneration [42]. The gene produces ATPase associated with various cellular activities (AAA) protein family protein paraplegin, required for cellular activities, along with axon regeneration [43].…”
Section: Chromosome 16mentioning
confidence: 99%
“…A heterozygous mutation in SPG7/PGN gene at 16q24 is characterised by extensive weakness and spasticity in lower extremities due to axonal degeneration [42]. The gene produces ATPase associated with various cellular activities (AAA) protein family protein paraplegin, required for cellular activities, along with axon regeneration [43].…”
Section: Chromosome 16mentioning
confidence: 99%
“…It indicated that Spastin M87V must have a complete microtubule binding domain (MTBD) and cutting function domain specific to microtubule (AAA). Spastin can bind to the stable functional domain of microtubules, anchor the sidewall of microtubules by MIT, bind to the C-terminal of tubulin with positively charged AAA ATP ring holes, destroy the palisade structure of microtubules and cuase long microtubules to bend and break into small segments of microtubules [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…AAA protein family has a highly conserved AAA functional domain consisting of 200 to 250 amino acids. The seventh sub-family contains three proteins: spastin, katanin and fidgetin [3][4][5]. At present, two kinds of microtubule cutting proteins, katanin and spastin, have been studied widely.…”
Section: Introductionmentioning
confidence: 99%